Combinatorial Image Analysis 16th International Workshop, IWCIA 2014, Brno, Czech Republic, May 28-30, 2014, Proceedings - Barneva, Reneta P.; Brimkov, Valentin E.; Slapal, Josef (Image Processing, Computer Vision, Pattern Recognition, and Graphics ;, 2014)
This volume constitutes the refereed proceedings of the 16th International Workshop on Combinatorial Image Analysis, IWCIA 2014, held in Brno, Czech Republic, in May 2014. The 20 revised full papers and 3 invited papers presented were carefully reviewed and selected from numerous submissions. The topics covered include discrete geometry and topology in imaging science, new results in image representation, segmentation, grouping, and reconstruction, medical image processing.